Integrated nutrient management in mango - A, Sable P; Saras, Piyush; Singh, Pushpraj; Patel, J R (Indian Horticulture, 2023)
Mango, the ‘King of Fruits’ (Mangifera indica L) is one of the most significant fruits produced in the tropics and sub-tropics of the globe. In mango, many problems are associated with fruit set, yield and quality due to inadequate nutrient management. Macronutrients as well as micronutrients are found equally essential for plant growth and development. Micronutrients play key role in enzymatic activities, assimilates synthesis and hormone synthesis. Their acute deficiencies some time, poses problems. Bio-fertilizers are used in live formulation for mobilizationand availability of nutrients particularly by their biological activity which helps in beneficial soil microorganism built up, thereby improving soil health. The use of organic manures, bio-fertilizers, micronutrients and recommended dose of fertilizers in mango orchard helps to enhance fruit production. This article highlights the details about integrated nutrient management in mango.